2021
DOI: 10.1186/s12913-021-06334-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical malpractice in Norway: frequency and distribution of disciplinary actions for medical doctors 2011–2018

Abstract: Background Physicians who perform unsafe practices and harm patients may be disciplined. In Norway, there are five types of disciplinary action, ranging from a warning for the least serious examples of malpractice to loss of licence for the most serious ones. Disciplinary actions always involve medical malpractice. The aims of this study were to investigate the frequency and distribution of disciplinary actions by the Norwegian Board of Health Supervision for doctors in Norway and to uncover na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Recently, a Norwegian study of the frequency and distribution of disciplinary actions for medical doctors found higher rates for physicians who work in small clinics or alone (GPs and private specialists) than for those working in large organizations (hospital doctors) [ 33 ]. This emphasizes the impact of systemic and structural factors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a Norwegian study of the frequency and distribution of disciplinary actions for medical doctors found higher rates for physicians who work in small clinics or alone (GPs and private specialists) than for those working in large organizations (hospital doctors) [ 33 ]. This emphasizes the impact of systemic and structural factors.…”
Section: Discussionmentioning
confidence: 99%
“…There are five possible disciplinary penalties; a warning is the least severe, and revocation or suspension of a license is the strongest form of punishment. The most common and serious violations by physicians include sexual misconduct, failure to comply with required standards of care, and unprofessional behavior [67].…”
Section: The Health and Socialmentioning
confidence: 99%
“…Young Norwegian GPs who undergo specialist training are entitled to formal supervision at regular intervals, but in daily life they manage a great number of complex patients and situations single-handedly, in contrast to peer colleagues in hospital settings. Even in a group practice, the working situation of a GP can therefore appear somewhat lonely [20][21][22][23][24][25][26][27]. Since 1994, the Institute for Studies of the Medical Profession in Norway has undertaken surveys to identify the health, quality of life and working conditions of Norwegian physicians, applying the effort-reward imbalance model.…”
Section: Introductionmentioning
confidence: 99%